DESAIN PEMBELAJARAN TEMATIK INTEGRATIF BERBASIS BUDAYA UNTUK MENINGKATKAN HASIL DAN KEBERMAKNAAN BELAJAR - Nur Chofifah; Stefanus C. Relmasira; Feprina Pinda (Jurnal Penelitian Humaniora, 2019)
This research aims to improve student learning outcomes and meaningfulness through the application of culture-based integrative thematic design. The type of research used is Stringer model class action research which is carried out through two stages by look, think, and act. Instruments record data using question instruments, questionnaires, art, and documentation. The subject of this research was  fourth grade students of SDN Salatiga 03. Data analysis was carried out with comparative descriptions. The results of the research showed an increase in the results and meaningfulness of student learning. This is shown in the completeness of the thematic learning outcomes in the contents of Indonesian and  Sciences in a row of 70% and 73% in the first cycle.  Furthermore, there was an increase of 82% and 88% in the second cycle. The results of the meaningfulness of student learning in the category are very significant in cycle I, which is 73% and increases in cycle II, which is 88%. Therefore, the application of culture-based integrative thematic learning can improve the results and meaningfulness of elementary school students' learning.